2000
DOI: 10.1038/sj.gt.3301329
|View full text |Cite
|
Sign up to set email alerts
|

Direct intra-cardiomuscular transfer of β2-adrenergic receptor gene augments cardiac output in cardiomyopathic hamsters

Abstract: In chronic heart failure, down-regulation of ␤-adrenergic receptor (␤-AR) occurs in cardiomyocytes, resulting in low catecholamine response and impaired cardiac function. To correct the irregularity in the ␤-AR system, ␤-AR gene was transduced in vivo into failing cardiomyocytes. The EpsteinBarr virus (EBV)-based plasmid vector carrying human ␤ 2 -AR gene was injected into the left ventricular muscle of Bio14.6 cardiomyopathic hamsters whose ␤-AR is downregulated in the cardiomyocytes. The echocardiographic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Although non-viral methods are free from virus-associated adverse effects, their transduction efficiency is low. For example, following direct intramyocardial injection of plasmid DNA into the heart of mice [3], rats [4,5], and hamsters [6], the transgenes were expressed only within a small area surrounding the injection site. A more efficient non-viral method of gene transfer is sonoporation of cells.…”
mentioning
confidence: 99%
“…Although non-viral methods are free from virus-associated adverse effects, their transduction efficiency is low. For example, following direct intramyocardial injection of plasmid DNA into the heart of mice [3], rats [4,5], and hamsters [6], the transgenes were expressed only within a small area surrounding the injection site. A more efficient non-viral method of gene transfer is sonoporation of cells.…”
mentioning
confidence: 99%
“…On the other hand, we have recently shown that naked EBV-based plasmid DNA was quite effective in transducing cardiac muscle. 22,29 When an EBV-based plasmid containing the ␤ 2 -adrenergic receptor gene was injected into the myocardium of cardiomyopathic hamsters, a significant elevation in cardiac output was obtained, suggesting a novel gene therapy strategy against heart failure. 22 The 'hydrodynamics-based procedure' may become an attractive approach for gene therapy of various diseases as well as functional, in vivo analysis of genes of interest.…”
Section: Gl3 and Pggl3 (Student's T Test)mentioning
confidence: 99%
“…[24][25][26][27] In some of these studies, the EBV-based plasmid vectors were combined with cationic liposomes, 25,28 cationic polymers, 23,[25][26][27]29 electroporation 21 or gene gun, 30 while in the other studies, naked EBV-based plasmid was injected into the cardiac muscle. 22,29 In the present study, we transferred the naked EBV-based plasmid vectors to the liver through the intravascular route.EBV-based and conventional plasmid vectors encoding the luciferase or ␤-gal genes as markers (Figure 1, upper panels) were constructed and injected intravenously into the tail vein of mice as described. 9 The injection with pG.GL3, a conventional luciferase-expression vector,…”
mentioning
confidence: 99%
See 2 more Smart Citations